Análisis de gestión de las pequeñas unidades productivas cacaoteras y el impacto económico en las familias, en el sector La Cadena, Cantón Valencia, Provincia de Los Ríos. - Palma Lucas, José Farid (2016)
Cocoa is one of the crops that sustain many families nationwide, however the administration of the production units can directly influence the expected results of this activity, as it can result in costs and inadequate processes. As it conducted this research to analyze the current situation of small cocoa industry chain and impact on the family economy productive units. The surveys were conducted in the parish of La Cadena, belonging to the canton Valencia province of Los Rios, considering 50 shows small cocoa farmers. The main results it was observed that small production units visited mostly are financed with equity, the same that are managed by its owner. Ignorance of the administrative process hinders farmers with good management, based on the work planning and other activities of the farm. He does not belong to any association hinders access of farmers to training plans that can better their administrative activity in their production units. The experience of workers in small production units is a strong case for crop management point, however not keep track of production, income and expenditure difficult to manage resources. Visited farms are mostly minor extensions to the 4 hectares, the same that have been acquired largely through inheritance, and 20% for the purchase. In the farms visited predominantly planting cacao CCN-51, which is highly productive, which represents a profitable opportunity for farmers, as long as it is good management, since their production is greater than 40 quintals per hectare per year, which is reflected in increased income to $ 4800.00 per year, considering a sale price of $ 110.00 per quintal. 46% of farmers whose sole livelihood selling cocoa, which allows access to basic services and support their families who mostly are made up of five members, whose expenditures ranging between $ 401.00 and $ 500.00 per month, ie they are not excessively high, so that the production of their farms can afford them monthly.